Stress dependent and redistribution behaviour of unbound granular material. Issue Volume 21:Issued 3(2020) (23rd February 2020) - Li, Shaohui; Hao, Peiwen
ABSTRACT: The paper is presented to investigate the tensile stress modification effect on unbound granular materials. The theory of tensile stress modification was proposed and discussed. Seven granular constitutive models were applied in finite element analysis and the calculated strains were compared and verified by results measured in the field. It is shown that the stress modification is essential to accurately predict pavement deformation. The distribution of stress attenuation factor in granular layer is plotted and discussed when Uzan model is applied in theory analysis. It is found that the convergent modulus of granular reduces significantly and the tensile stress or strain at the bottom of asphalt layer increases as a result of the stress modification effect.